Penyerapan Tenaga Kerja Sektor Konstruksi di Indonesia (Studi pada 6 Provinsi di Jawa) - Herman Cahyo Diartho; Ma'ruf Hanuraga (MediaTrend, 2018)
Labor absorption can be measured by using the Provincial Minimum Wage (UMP) rate. The greater the value of wages earned is expected to affect the level of labor productivity. In this study aims to determine the effect of Province Minimum Wage on employment absorption of the construction sector. This research is qualitative and quantitative research. Qualitative analysis uses prescriptive analysis while quantitative analysis using method PanelLeast Square (PLS). The data used are time series (year 2006-2015) and cross section (6 provinces in Java). The type of data used in this study is secondary data obtained from the Central Statistic Agency (BPS) and the journal as a supporter. The analysis method used is linear regression analysis method of panel data with Random Effect Model (REM). The results show that, Minimum Wage variable Province has a positive influence with coefficient of 1.7671 and probability of 0.3538 to the absorption of labor in 6 provinces of Java Island in 2006-2015.